KALIGRAFI ARAB TENTANG KEESAAN ALLAH DALAM KARYASERIGRAPHY - ERGA PONI, Drs. Syafei, M.Ag, Yofita Sandra, S.Pd., M.Pd (Serupa The Journal of Art Education, 2015)
The word of Calligraphy comes from the French word which calligraphie where as the Greek word meaning called kalligraphia beautiful hand writing. Calligraphy obtain the highest position and is an expression of the spirit of Islam that is very typical. Calligraphy has two main attraction, namely the Al-Quran verses contained there in and the beauty style of letter. Calligraphy that has an appeal that is so high, it is necessary to use the maximum of calligraphy that for a kindness. With so many in this world polytheism Qur'anic verse about oneness of Allah has religious significance as a function to awaken mankind. For this reason, the authors are interested in creating works with the theme "On the Unity of Allah Arabic Calligraphy In serigraphy work". In the process embodiment of this work, the author show pure art work using screen printing graphic art with tools and material preparation phase, stabilization, and the realization and settlement. Writers produce 10 works of the oneness of Allah, among others Surah Al-Ikhlas, Paragraph 1-4), Shock (Az-Zalzalah), the Book of Allah and devotion (Surah Al-Baqharah, Paragraphs 1 and 2), Seawater (Surah Ar-Rahman , Paragraph 19), meeting of 2 water (Surah ar-Rahman, paragraph 20), Deeds (Surah As-Shafaat, Paragraph 96), Revelation and Revenge in the Hereafter (Surah Shaad, verse 66), Revelation and Revenge in the Hereafter (Surah Shaad, Paragraph 67), Revelation and Revenge in the Hereafter (Surah Shaad, verse 68), Faith (Letters Dzaryaat, Verse 20).Keywords: Calligraphy, the unity of Allah, serigraphy